(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
Vetiver (Vetiveria zizanioides Nash), a hedge-forming grass with hightolerance to salinity, was grown from root divisions in pots containing sandy soil, at theFaculty of Agriculture, University of Khartoum, Sudan. Four levels of Red Sea watermixed with fresh water were used in the following ratios of sea water to fresh water: 0:1(EC, 0.4 dSm-1 ) as a control, 1:20 (EC, 3.1 dSm-1), 1:10 (EC, 5.5 dSm-1) and 1:5 (EC, 9.3dSm-1 ). Depending on the level of salinity suberization was induced to varying degreesin the stele including that of the pericycle, protoxylem elements, and phloem. This mayhave contributed to the death of plants under the highest level of sea water.